Small bowel adenocarcinoma: French intergroup clinical practice guidelines for diagnosis, treatments and follow-up (SNFGE, FFCD, GERCOR, UNICANCER, SFCD, SFED, SFRO). Issue 1 (January 2018) - Locher, Christophe; Batumona, Blaise; Afchain, Pauline; Carrère, Nicolas; Samalin, Emmanuelle; Cellier, Christophe; Aparicio, Thomas; Becouarn, Yves; Bedenne, Laurent; Michel, Pierre; Parc, Yann; Pocard, Marc; et al.
Abstract: Background: This document is a summary of the French intergroup guidelines regarding the management of small bowel adenocarcinoma published in October 2016. Method: This collaborative work, co-directed by most French Medical Societies, summarizes clinical practice recommendations (guidelines) on the management of small bowel adenocarcinoma. Given the lack of specific data in the literature, all references are given by analogy with colon cancer. The classification used is the AJCC (American Joint Committee on Cancer) pTNM classification (7th edition 2009). Results: Small bowel adenocarcinoma has a poor prognosis; less than 30% of patients survive for 5 years after the (first) diagnosis (5-year survival of less than 30%). Due to the rarity of the disease and the retrospective data, most recommendations are based on expert agreement. The initial evaluation is based on chest-abdomen-pelvis CT scan, CEA assay, GI endoscopy and colonoscopy in order detect lesions associated with a predisposing disease. Surgical treatment is currently the only curative option for stage I and II. Adjuvant chemotherapy can be discussed for Stage III and Stage II with T4 (expert agreement). With regard to metastatic tumors, treatment with fluoropyrimidine combined with platinum salts should be considered (expert agreement). Conclusion: Few specific data exist in the literature on this type of tumor; most of the recommendations come from expert agreements or by analogy with colon cancer. Thus, each case must be discussed within a multidisciplinary team.